Method for preparing LAGP solid electrolyte based on coprecipitation method
Through the combined sintering technique of alternately switched by the co-sedimentation method and oxidation-restore atmosphere, the problem of insufficient density of traditional LAGP solid electrolytes, and realized LAGP electrolyte materials with high ion conductivity and thermal stability.
Patent Information
- Application Number
- CN202411622918.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-28
Smart Images

Figure CN119381532A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of LAGP solid electrolyte preparation, and specifically relates to a method for preparing LAGP solid electrolyte based on a coprecipitation method. Background Art
[0002] LAGP solid electrolyte is an important component of lithium-ion batteries because it exhibits a high -4 Up to 10 -3 S / cm high ionic conductivity, and excellent chemical stability, can maintain good electrochemical performance during battery operation, so it has become a hot research topic in the field of solid electrolytes. LAGP electrolytes can effectively solve the problems of leakage, poor thermal stability and interface side reactions in traditional liquid electrolytes, especially in high-safety, long-life solid-state batteries. However, traditional LAGP solid electrolyte preparation methods, such as high-temperature solid-phase method and sol-gel method, often have problems such as insufficient material density, high porosity and poor contact between particles, resulting in low ionic conductivity of the overall material. This is mainly because these methods are difficult to effectively sinter dense crystal structures at low temperatures, and are prone to material agglomeration, grain boundary defects and other problems during the sintering process, which hinders the transmission of ions inside the crystal. In addition, the formation of secondary phases or impurities in the material may further reduce its conductivity.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for preparing LAGP solid electrolyte based on a co-precipitation method, thereby solving the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:
[0006] A method for preparing LAGP solid electrolyte based on coprecipitation method comprises the following steps:
[0007] Step (1): weighing germanium dioxide, a lithium source, an aluminum source and a phosphorus source according to a stoichiometric ratio;
[0008] Step (2): mixing germanium dioxide and a lithium source and dissolving them in deionized water to form a uniform first mixed solution;
[0009] Step (3): adding a precipitant to the first mixed solution, adjusting the pH value of the first mixed solution to 8-10, and forming a precursor precipitate solution;
[0010] Step (4): Add aluminum source and phosphorus source to the precursor precipitate solution in sequence, and apply an electric field of 5-50V / cm to control the Ge 4+ , Li + 、Al 3+ and PO4 3- The movement direction of the ions is such that the aluminum source, the phosphorus source, the germanium source, and the lithium source in the precursor solution fully react to form a uniform second mixed solution;
[0011] Step (5): placing the second mixed solution in a water bath at 60-80° C. and continuously stirring the reaction until the solution is completely evaporated to form LAGP precursor powder;
[0012] Step (6): The obtained LAGP precursor powder is mixed with PVDF-HFP powder in a ratio of 10-30% to form a uniform mixture, and the first stage sintering is carried out at a temperature of 150-300°C under the protection of an oxidizing atmosphere, and the temperature is kept for 0.5-3 hours; the alternating switching of the oxidizing and reducing atmospheres can effectively promote the growth of grains and the densification of the crystal phase during the sintering process. The reducing atmosphere can prevent excessive oxidation of the material at high temperatures, while the oxidizing atmosphere helps to form a stable crystal structure. Under the combined action of the oxidizing and reducing atmospheres, a more dense and uniform material structure can be formed, thereby improving the mechanical strength and conductivity of the material. In the process of alternating switching between the oxidizing and reducing atmospheres, the oxidizing atmosphere helps to repair surface defects of the material, such as vacancies or other lattice defects, while the reducing atmosphere can prevent excessive oxidation of metal oxides (such as lithium or aluminum) under high temperature conditions, thereby improving the crystal quality and chemical stability of the material. Alternating atmosphere switching can promote the formation of a stable phase boundary inside the material, help optimize the continuity and uniformity of the ion channel, and further improve the ionic conductivity of the material. At the same time, the material is prevented from being oxidized or over-reduced during the sintering process, ensuring the high ionic conductivity and high thermal stability of the LAGP solid electrolyte.
[0013] Step (7): After the first stage sintering, the mixture is heated to 600-850° C. at a heating rate of 1-10° C. / min in a reducing atmosphere, and the mixture is sintered in the second stage, and kept at this temperature for 1-8 hours, and then cooled to room temperature to obtain a LAGP solid electrolyte;
[0014] Step (8): After sintering, the LAGP electrolyte is surface irradiated by an argon ion beam.
[0015] Preferably, in step (8), the irradiation energy is 1-5 MeV and the duration is 5-30 minutes.
[0016] Preferably, in step (7), the oxidizing atmosphere and the reducing atmosphere are alternately switched every 8-10 minutes, wherein the reducing atmosphere is one of nitrogen and hydrogen, and the oxidizing atmosphere is oxygen.
[0017] Preferably, the concentration of the first mixed solution is 0.1-0.5 mol / L, and the concentration of the second mixed solution is 0.1-0.3 mol / L.
[0018] Preferably, the lithium source is one of lithium hydroxide, lithium carbonate or lithium nitrate, the aluminum source is one of aluminum nitrate, aluminum sulfate or aluminum carbonate, the phosphorus source is one of diammonium phosphate, phosphoric acid or diammonium hydrogen phosphate, and the precipitant is one of ammonia water or an ammonium salt.
[0019] Preferably, the particle size of the LAGP solid electrolyte is less than 150 nm.
[0020] Preferably, Ge 4+ , Li + and Al 3+ Under the action of the external electric field, the cations will move toward the negative electrode, PO4 3- It is a negatively charged anion. Under the action of an electric field, the anion will move toward the positive electrode.
[0021] Preferably, the stoichiometric ratio of germanium dioxide, lithium source, aluminum source and phosphorus source is Li 1.5 Al 0.5 Ge 1.5 (PO4)3.
[0022] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:
[0023] The present invention utilizes electric field assisted precipitation method to make Ge 4+ , Li + 、Al 3+ and PO4 3- During the precipitation process, the ions move in the specified polarity direction, thereby being evenly distributed in the reaction solution. This process effectively avoids non-uniform reactions caused by ion aggregation or local uneven concentrations. In addition, the application of the electric field ensures the synchronous precipitation of different ions, prompting the components in the precursor powder to combine precisely in an ideal ratio. At the same time, the co-precipitation conditions are further optimized by adjusting the pH value to 8-10. Within this range, the reaction is relatively stable, which can effectively inhibit the formation of impurities or unnecessary side reactions, and ensure the chemical purity and uniformity of the precursor.
[0024] After the precursor is generated, the present invention dopes 10-30% of PVDF-HFP powder as a binder, which not only improves the density of the material during the sintering process, but also effectively inhibits the agglomeration of LAGP particles, ensuring good connection between particles. During the sintering process, the temperature of the first stage is controlled at 150-300°C, which helps to remove moisture and volatile substances in the precursor, creating favorable conditions for the second stage high-temperature sintering; and the second stage sintering at 600-850°C further promotes the crystal phase transformation of LAGP powder, forming a denser and purer crystal structure, and enhancing its ionic conductivity.
[0025] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0027] In the figure:
[0028] Figure 1 This is a SEM image of the LAGP solid electrolyte prepared in Example 1 of the present invention;
[0029] Figure 2 This is a SEM image of the LAGP solid electrolyte prepared in Example 2 of the present invention;
[0030] Figure 3 This is a SEM image of the LAGP solid electrolyte prepared in Example 3 of the present invention;
[0031] Figure 4 This is a SEM image of the LAGP solid electrolyte prepared in Example 1 of the present invention;
[0032] Figure 5 This is a SEM image of the LAGP solid electrolyte prepared in Example 3 of the present invention;
[0033] Figure 6 This is a SEM image of the LAGP solid electrolyte prepared in Example 3 of the present invention;
[0034] Figure 7 This is a SEM image of the LAGP solid electrolyte prepared in Example 3 of the present invention;
[0035] Figure 8 This is a SEM image of the LAGP solid electrolyte prepared in Example 2 of the present invention.
[0036] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0038] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0039] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0040] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0042] See also Figure 1-8 As shown, in this embodiment, a method for preparing LAGP solid electrolyte based on coprecipitation method is provided, comprising the following steps:
[0043] Step (1): weighing germanium dioxide, a lithium source, an aluminum source and a phosphorus source according to a stoichiometric ratio;
[0044] Step (2): mixing germanium dioxide and a lithium source and dissolving them in deionized water to form a uniform first mixed solution;
[0045] Step (3): adding a precipitant to the first mixed solution, adjusting the pH value of the first mixed solution to 8-10, and forming a precursor precipitate solution;
[0046] Step (4): Add aluminum source and phosphorus source to the precursor precipitate solution in sequence, and apply an electric field of 5-50V / cm to control the Ge 4+ , Li + 、Al 3+ and PO4 3- The movement direction of the ions is such that the aluminum source, the phosphorus source, the germanium source, and the lithium source in the precursor solution fully react to form a uniform second mixed solution;
[0047] Step (5): placing the second mixed solution in a water bath at 60-80° C. and continuously stirring the reaction until the solution is completely evaporated to form LAGP precursor powder;
[0048] Step (6): mixing the obtained LAGP precursor powder and PVDF-HFP powder in a ratio of 10-30% to form a uniform mixture, and performing the first stage sintering at a temperature of 150-300° C. under the protection of an oxidizing atmosphere for 0.5-3 hours;
[0049] Step (7): After the first stage sintering, the mixture is heated to 600-850° C. at a heating rate of 1-10° C. / min in a reducing atmosphere, and the mixture is sintered in the second stage, and kept at this temperature for 1-8 hours, and then cooled to room temperature to obtain a LAGP solid electrolyte;
[0050] Step (8): After sintering, the LAGP electrolyte is surface irradiated by an argon ion beam.
[0051] In this embodiment, the irradiation energy in step (8) is 1-5 MeV, and the duration is 5-30 minutes.
[0052] In the present embodiment, in step (7), the oxidizing atmosphere and the reducing atmosphere are alternately switched every 8-10 minutes, wherein the reducing atmosphere is one of nitrogen and hydrogen, and the oxidizing atmosphere is oxygen.
[0053] In this embodiment, the concentration of the first mixed solution is 0.1-0.5 mol / L, and the concentration of the second mixed solution is 0.1-0.3 mol / L.
[0054] In this embodiment, the lithium source is one of lithium hydroxide, lithium carbonate or lithium nitrate, the aluminum source is one of aluminum nitrate, aluminum sulfate or aluminum carbonate, the phosphorus source is one of diammonium phosphate, phosphoric acid or diammonium hydrogen phosphate, and the precipitant is one of ammonia water or an ammonium salt.
[0055] In this embodiment, the particle size of the LAGP solid electrolyte is less than 150 nm.
[0056] In this embodiment, Ge 4+ , Li + and Al 3+ Under the action of the external electric field, the cations will move toward the negative electrode, PO4 3- It is a negatively charged anion. Under the action of an electric field, the anion will move toward the positive electrode.
[0057] In this embodiment, the stoichiometric ratio of germanium dioxide, lithium source, aluminum source and phosphorus source is Li 1.5 Al 0.5 Ge 1.5 (PO4)3.
[0058] The present invention will now be further described in detail with reference to embodiments.
[0059] It should be noted that all raw materials in the examples of the present invention were obtained through commercial sources.
[0060] Example 1: In this example, a method for preparing a LAGP solid electrolyte based on a coprecipitation method is provided, comprising the following steps:
[0061] Step (1): Follow Li 1.5 Al 0.5 Ge 1.5 The stoichiometric ratio of (PO4)3 was 1.5 moles of germanium dioxide, 1.5 moles of lithium hydroxide, 0.5 moles of aluminum nitrate and 3 moles of diammonium phosphate.
[0062] Step (2): dissolving germanium dioxide and lithium hydroxide in deionized water to form a uniform first mixed solution with a concentration of 0.2 mol / L.
[0063] Step (3): Add 2 mol / L ammonia water to the first mixed solution to adjust the pH value to 9 to form a precursor precipitation solution.
[0064] Step (4): 0.5 mol of aluminum nitrate and 3 mol of ammonium dihydrogen phosphate were added to the precursor precipitate solution, and an electric field with a strength of 30 V / cm was applied to control the Ge 4+ , Li + 、Al 3+ and PO4 3- The direction of movement of the ions, after the reaction is completed, a second mixed solution is formed.
[0065] Step (5): The second mixed solution was stirred and reacted in a water bath at 70° C. for 2 hours until the solution was completely evaporated to obtain LAGP precursor powder.
[0066] Step (6): Mix the LAGP precursor powder with 20% PVDF-HFP powder, place it at 200° C. for the first stage sintering, and keep it warm for 1 hour. Use oxygen atmosphere protection during the first stage sintering process.
[0067] Step (7): After the first stage of sintering is completed, switch to nitrogen, heat up to 700°C at a heating rate of 5°C / min, perform the second stage of sintering, and keep at 700°C for 4 hours. Then, during the sintering process at 700°C, alternately switch the atmosphere every 8-10 minutes, using oxygen and nitrogen respectively.
[0068] Step (8): After sintering is completed, the material is cooled to room temperature to obtain a LAGP solid electrolyte.
[0069] Step (9): After sintering, the LAGP electrolyte is irradiated with an argon ion beam with an energy of 3 MeV for 20 minutes to improve the surface conductivity of the material.
[0070] Example 2: In Example 2, in step (6), LAGP precursor powder is mixed with 30% PVDF-HFP powder to form a uniform mixture.
[0071] Example 3: In Example 3, in step (6), the LAGP precursor powder is mixed with 20% PVDF-HFP powder, and the first stage sintering temperature of step (7) is 250° C. and the holding time is 2 hours.
[0072] In step (8), the heating rate is adjusted to 3°C / min, the temperature is raised to 800°C, the heat preservation time is 6 hours, and hydrogen is used as the reducing atmosphere.
[0073] Comparative Example: In the comparative example, germanium dioxide and lithium hydroxide were dissolved in deionized water to form a first mixed solution with a concentration of 0.2 mol / L, but the pH value was not adjusted, and the coprecipitation reaction was directly carried out without applying an electric field or adding PVDF-HFP powder. The temperature during the sintering process was the same as that in Example 1, but oxygen and hydrogen were not used. Finally, no argon ion beam irradiation was performed.
[0074] 1. Ionic conductivity test
[0075] Equipment: Electrochemical workstation or impedance spectrometer
[0076] During the test, first, the prepared LAGP solid electrolyte was pressed into a circular sheet with a diameter of about 10 mm and a thickness of 1-2 mm. Next, gold electrodes were coated on both sides of the sample, and the electrodes were brought into close contact with the sample by a press. Subsequently, the sample was loaded into the electrode fixture of the EIS device, and the test temperature was set to room temperature. The test frequency range was set to 1MHz-1Hz, and then a 10mV voltage was applied. The EIS data was recorded and analyzed, the Nyquist plot was obtained, the resistance value of the sample was calculated, and the ionic conductivity was calculated using the following formula: Where, σ is the ionic conductivity (S / cm), L is the sample thickness (cm), R is the resistance value obtained from the Nyquist plot (Ω), and A is the surface area of the sample (cm 2 ).
[0077] 2. Surface conductivity analysis
[0078] Equipment: Electrochemical workstation or surface conductivity tester
[0079] During the test, first, the LAGP solid electrolyte sample after sintering was irradiated with an argon ion beam. Then, the treated sample was subjected to electrochemical impedance spectroscopy to determine the surface conductivity of the sample, wherein the steps of the electrochemical impedance spectroscopy test were the same as those of the ion conductivity test.
[0080] 3. Thermal stability test
[0081] Equipment: Thermogravimetric analyzer
[0082] During the test, first, place the sample on the sample tray of the TGA equipment. Set the temperature range from room temperature to 800°C, and the heating rate is 10°C / min. Run TGA and record the weight change of the sample with temperature. Analyze the thermal stability of the sample through the thermogravimetric curve and observe the mass loss of the sample under high temperature conditions.
[0083] The test results of the above ionic conductivity test, surface conductivity analysis, and thermal stability test are shown in Table 1.
[0084] Table 1: Comparison table of Examples 1-3 and Control Examples
[0085]
[0086] It can be seen from Table 1 that the ionic conductivity of Example 1, Example 2 and Example 3 is 6.0×10 -4 S / cm, 6.2×10 -4 S / cm and 6.5×10 -4 S / cm, significantly higher than the control sample of 3.5×10 -4S / cm, which shows that PVDF-HFP as a binder can effectively improve the density of the material, reduce grain boundary impedance, and thus enhance ionic conductivity. When the PVDF-HFP ratio in Example 2 is increased to 30%, the conductivity is slightly improved, indicating that an appropriate amount of PVDF-HFP helps to improve the electrolyte performance. Example 3 uses a higher sintering temperature (800°C) and an oxidation-reduction atmosphere switch to form a denser crystal phase and optimized ion channels, further improving the conductivity.
[0087] After argon ion beam irradiation, the surface conductivity of Examples 1-3 was further improved, reaching 7.0×10 -4 S / cm, 7.2×10 -4 S / cm and 7.5×10 -4 S / cm. The surface conductivity of LAGP is significantly improved after irradiation. Argon ion beam can eliminate surface defects, improve surface microstructure and increase conductivity.
[0088] Thermogravimetric analysis (TGA) of Examples 1-3 shows that the decomposition temperatures of Examples 1-3 are 450°C, 460°C and 470°C, respectively, while the decomposition temperature of the control example is 400°C, and the mass loss is also significantly larger. It can be seen that PVDF-HFP can not only enhance ionic conductivity, but also improve the thermal stability of the material. As the proportion of PVDF-HFP increases (such as 30% in Example 2), the decomposition temperature of the material increases and the mass loss decreases. Moreover, it can be seen from Example 3 that a higher sintering temperature can promote the densification of the crystal structure and reduce the risk of thermal decomposition of the material.
[0089] like Figure 1 , 4 As shown, due to the low sintering temperature of Example 1, the particle size is relatively large, about 130-150nm. The grain boundaries are relatively obvious, but due to the low temperature, the surface of some particles still appears relatively rough, with more pores, and the density of the crystal is relatively general.
[0090] like Figure 2 , 8 As shown, at a sintering temperature of 750°C, the particle size of Example 2 is further reduced to about 120nm compared to Example 1. High-temperature sintering promotes the refinement of particles, making the grain boundaries clearer, the particles more tightly bonded, and the overall density significantly improved. During the sintering process, the pores between the particles are effectively filled, the pore structure of the material is more uniform, the internal voids and possible defects are reduced, and the ion conduction path is optimized. In addition, the higher temperature makes the particle surface smoother, and the surface defects and roughness are improved. The smooth surface is conducive to good contact between the electrolyte and the electrode, thereby reducing the interfacial impedance and improving the electrochemical performance of the battery.
[0091] like Figure 3 , 5 As shown in Figures 6 and 7, in Example 3, under high-temperature sintering conditions of 850°C, the particle size of the LAGP solid electrolyte is further reduced to about 115nm, the crystal structure is significantly densified, the porosity is greatly reduced, and the surface presents a smoother and more uniform characteristic. High-temperature sintering not only promotes the refinement of the particles, but also enhances the close packing between the particles, making the grain boundaries clearer and effectively eliminating the gaps between the particles. This dense structure provides a continuous channel for the smooth transmission of ions, thereby improving the ionic conductivity of the material. In addition, the densification and uniform particle arrangement significantly improve the mechanical strength of the material, giving it better stability and resistance to deformation during use.
[0092] The microstructure diagram shows the microstructural changes brought about by these high-temperature treatments, especially the uniform distribution and densification of particles, which lays a solid foundation for the application of LAGP materials in high-performance lithium-ion batteries. Compared with traditional lower-temperature sintering, high-temperature treatment at 850°C significantly optimizes the internal structure and surface properties of the material, which not only helps to reduce interfacial impedance, but also effectively improves the stability of the material during charging and discharging, and reduces the problem of battery performance degradation caused by uneven electrolyte structure. Therefore, this LAGP electrolyte material optimized by high-temperature sintering exhibits better electrochemical properties and mechanical strength, and has the potential to be widely used in future solid-state lithium batteries.
[0093] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.
Claims
1. A method for preparing LAGP solid electrolyte based on coprecipitation method, characterized in that: The following steps are involved: Step (1): weighing germanium dioxide, a lithium source, an aluminum source and a phosphorus source according to a stoichiometric ratio; Step (2): mixing germanium dioxide and a lithium source and dissolving them in deionized water to form a uniform first mixed solution; Step (3): adding a precipitant to the first mixed solution, adjusting the pH value of the first mixed solution to 8-10, and forming a precursor precipitate solution; Step (4): Add aluminum source and phosphorus source to the precursor precipitate solution in sequence, and apply an electric field of 5-50V / cm to control the Ge 4+ , Li + 、Al 3+ and PO4 3- The movement direction of the ions is such that the aluminum source, the phosphorus source, the germanium source, and the lithium source in the precursor solution fully react to form a uniform second mixed solution; Step (5): placing the second mixed solution in a water bath at 60-80° C. and continuously stirring the reaction until the solution is completely evaporated to form LAGP precursor powder; Step (6): mixing the obtained LAGP precursor powder and PVDF-HFP powder in a ratio of 10-30% to form a uniform mixture, and performing the first stage sintering at a temperature of 150-300° C. under the protection of an oxidizing atmosphere for 0.5-3 hours; Step (7): After the first stage sintering, the mixture is heated to 600-850° C. at a heating rate of 1-10° C. / min in a reducing atmosphere, and the mixture is sintered in the second stage, and kept at this temperature for 1-8 hours, and then cooled to room temperature to obtain a LAGP solid electrolyte; Step (8): After sintering, the LAGP electrolyte is surface irradiated by an argon ion beam.
2. A method for preparing LAGP solid electrolyte based on coprecipitation method according to claim 1, characterized in that: In step (8), the irradiation energy is 1-5 MeV and the duration is 5-30 minutes.
3. A method for preparing LAGP solid electrolyte based on coprecipitation method according to claim 1, characterized in that: In step (7), the oxidizing atmosphere and the reducing atmosphere are alternately switched every 8-10 minutes, wherein the reducing atmosphere is one of nitrogen and hydrogen, and the oxidizing atmosphere is oxygen.
4. A method for preparing LAGP solid electrolyte based on coprecipitation method according to claim 1, characterized in that: The concentration of the first mixed solution is 0.1-0.5 mol / L, and the concentration of the second mixed solution is 0.1-0.3 mol / L.
5. The method for preparing LAGP solid electrolyte based on coprecipitation method according to claim 1, characterized in that: The lithium source is one of lithium hydroxide, lithium carbonate or lithium nitrate, the aluminum source is one of aluminum nitrate, aluminum sulfate or aluminum carbonate, the phosphorus source is one of diammonium phosphate, phosphoric acid or diammonium hydrogen phosphate, and the precipitant is one of ammonia water or an ammonium salt.
6. A method for preparing LAGP solid electrolyte based on coprecipitation method according to claim 1, characterized in that: The particle size of LAGP solid electrolyte is less than 150nm.
7. The method for preparing LAGP solid electrolyte based on coprecipitation method according to claim 1, characterized in that: Ge 4+ , Li + and Al 3+ Under the action of the external electric field, the cations will move toward the negative electrode, PO4 3- It is a negatively charged anion. Under the action of an electric field, the anion will move toward the positive electrode.
8. The method for preparing LAGP solid electrolyte based on coprecipitation method according to claim 1, characterized in that: The stoichiometric ratio of germanium dioxide, lithium source, aluminum source and phosphorus source is Li 1.5 Al 0.5 Ge 1.5 (PO4)3.